The LBW Reviewed From Nutritional And Parity Nutritional Status Of Pregnant Mother - Nur Hamida (Journal of Applied Nursing and Health, 2019)
Low birth weight babies are more prone to possible growth barriers, changes in body proportions and a number of metabolic and cardiovascular changes. In addition, low birth weight babies will also have a higher risk of mortality and morbidity, malnutrition, short or thin problems during their childhood. The nutritional status of pregnant women greatly affects the growth of the fetus being conceived. Purpose of knowing LBW incidence in terms of nutritional status of pregnant women and parity of pregnant women in the perinatology room of RSUD Undata Palu, Central Sulawesi Province The design used in the study is Retrospective. Population is All Babies and Mothers in the Peritology Room of Rsud Undata Palu. The sample size was 35 respondents using the Independent Variable Purposive sampling technique. The research was nutritional status and maternal parity. The dependent variable is the incidence of LBW. Data was collected using a questionnaire, then the data were analyzed using logistic regression tests with a significance level of α ≤ 0.05. The results showed that almost half of respondents had 2-4 pregnancies as many as 17 respondents (48.6%), had good nutrition as many as 24 respondents (68.6%), not LBW as many as 28 respondents (80%). Test Statistics found that the significance value of p value from the wald test was 0.001. The results of the next statistical test found that p <a with a value of <0.05, this can be seen in Overall Statistics with a significance value of (p) 0.005 which means that there are variables that affect the incidence of LBW There is a relationship between LBW incidence in terms of nutritional status of pregnant women and parity of pregnant women in the perinatology room of RSUD Undata Palu, Central Sulawesi Province.